Metabolomic analysis reveals dynamic changes in secondary metabolites of Sophora japonica L. during flower maturation - Wang, Ji-Rui; Song, Xu-Hong; Li, Long-Yun; Gao, Si-Jia; Shang, Fang-Hong; Zhang, Xiao-Mei; Yang, Yong (Frontiers in Plant Science, 2022)
Sophora japonica L. is widely consumed in China for its medicinal and nutritional values. Its quality is greatly affected by the accumulation of metabolites, which vary with the stage of flower development. However, the characteristics of secondary metabolites during flower maturity remain unclear. Ultra-high-performance liquid chromatography coupled with electrospray ionization-triple quadrupole-linear ion trap mass spectrometry (UPLC–ESI–QTRAP–MS/MS) revealed dynamic changes in the secondary metabolites of S. japonica during in the five flower-maturity stages. We monitored 331 metabolites and screened 164 differential metabolites. The differential metabolites showed seven trends during flower maturation, with flavonoids and phenolic acids having the most varied expression. Flower buds (S2–S3) were rich in flavonoids and thus suitable for use in high-quality medicines or industrial extraction. Our study provides an empirical basis for the informed harvesting of S. japonica based on the mode of utilization.